Analysis of clonal expansions through the normal and premalignant human breast epithelium reveals the presence of luminal stem cells. Issue 1 (23rd November 2017) - Cereser, Biancastella; Jansen, Marnix; Austin, Emily; Elia, George; McFarlane, Taneisha; van Deurzen, Carolien HM; Sieuwerts, Anieta M; Daidone, Maria G; Tadrous, Paul J; Wright, Nicholas A; Jones, Louise; McDonald, Stuart AC
Abstract: It is widely accepted that the cell of origin of breast cancer is the adult mammary epithelial stem cell; however, demonstrating the presence and location of tissue stem cells in the human breast has proved difficult. Furthermore, we do not know the clonal architecture of the normal and premalignant mammary epithelium or its cellular hierarchy. Here, we use deficiency in the mitochondrial enzyme cytochrome c oxidase (CCO), typically caused by somatic mutations in the mitochondrial genome, as a means to perform lineage tracing in the human mammary epithelium. PCR sequencing of laser‐capture microdissected cells in combination with immunohistochemistry for markers of lineage differentiation was performed to determine the clonal nature of the mammary epithelium. We have shown that in the normal human breast, clonal expansions (defined here by areas of CCO deficiency) are typically uncommon and of limited size, but can occur at any site within the adult mammary epithelium. The presence of a stem cell population was shown by demonstrating multi‐lineage differentiation within CCO‐deficient areas. Interestingly, we observed infrequent CCO deficiency that was restricted to luminal cells, suggesting that niche succession, and by inference stem cell location, is located within the luminal layer. CCO‐deficient areas appeared large within areas of ductal carcinoma in situ, suggesting that the rate of clonal expansion was altered in the premalignant lesion. © 2017 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.